2018
DOI: 10.1186/s41155-018-0089-9
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral problems of school children: impact of social vulnerability, chronic adversity, and maternal depression

Abstract: This study's objective was to identify the predictive effect of indicators concerning social vulnerability, chronic adversity, and maternal depression on behavioral problems among school-aged children, according to the perceptions of mothers and teachers, considering the presence or absence of difficulties in the contexts of family and school. A total of 85 pairs of mothers and school children were distributed into three groups according to the behavioral problems identified. A General Questionnaire, the PHQ-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 40 publications
(56 reference statements)
2
14
0
4
Order By: Relevance
“…Although Martineli et al 39 have found the current maternal depression as a stronger predictor variable for the presence of internalizing and externalizing child behaviors, the cumulative and chronic adversities may contribute to behavioral problems. Some studies selected in this review support the association between maternal depression and children's internalizing behavior.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although Martineli et al 39 have found the current maternal depression as a stronger predictor variable for the presence of internalizing and externalizing child behaviors, the cumulative and chronic adversities may contribute to behavioral problems. Some studies selected in this review support the association between maternal depression and children's internalizing behavior.…”
Section: Discussionmentioning
confidence: 92%
“…The results were analyzed according to the descriptors. The studies in this review predominantly elected maternal depression as the main impact factor on child behavior [28][29][30][31][32]34,[38][39][40][41][42][43][44][45][46][47][48] . Both in cross-sectional and longitudinal studies there are an association between maternal and children behavioral problems in general.…”
Section: Discussionmentioning
confidence: 99%
“…The behavior of adolescents is a significant indicator of adaptation during this developmental stage (Martineli et al, 2018). However, some adolescents (between 6% to 66% [Kumar et al, 2016;Malhotra & Patra, 2014;Nair et al, 2017;Paul & Khan, 2019]) are not successful and may present numerous behavioral problems leading toward adverse consequences including poor school performance, high dropout rate, low self-esteem, loneliness, maladaptive coping and emotion regulation, poor adjustment, and quality of life (Agh et al, 2016;Kumar, 2019;Selamu & Singhe, 2018;Sutherland, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Embora os professores geralmente também relatem sobre a presença de mais problemas comportamentais por parte de crianças que convivem com a depressão materna, eles tendem a relatar a presença de mais problemas externalizantes e menos problemas internalizantes, em comparação à avaliação dos pais (Martineli et al, 2018). Pode-se considerar que os dados sobre a maior exposição das crianças com sintomas emocionais à disciplina relaxada das mães, e das crianças com problemas de conduta ao abuso físico, são concordantes com a literatura, na qual alguns estudos mostram a associação entre práticas de pouco envolvimento ou baixo controle comportamental e a presença de sintomas internalizantes por parte das crianças (Nunes et al, 2013), e entre práticas de abuso ou punição física e a presença de sintomas externalizantes (Callender et al, 2012;Piché et al, 2011a (Martineli et al, 2018;De Los Reyes et al, 2015;Stivanin et al, 2008). Ainda assim, considerando os dados combinados, de avaliadores diferentes, identificou-se uma concordância no que se refere à influência das práticas negativas para o comportamento infantil, bem como da disciplina relaxada para os sintomas emocionais, e do abuso físico para os problemas de conduta, o que coloca em destaque tais variáveis.…”
Section: Discussão 155unclassified